The Distribution of heavy metals in Jakarta and Semarang bay during the period of 2016 - 2019 - Yudi Nurul Ihsan; Phobe Nadine Alfa Zefa; Kalysta Fellatami; Mega Laksmini Syamsuddin; Sheila Zallesa (Depik, 2022)
Coastal areas have an important role and have high natural resources that can be utilized for human life. Over time, the increase in population is directly proportional to the activities and utilization of coastal areas, which puts great pressure on coastal areas. One of the pressures that occur in coastal areas is heavy pollution. This research aims to see the distribution of heavy metals especially Cd, Cu and Pb in the coastal areas of Jakarta Bay and Semarang Bay and to see the differences in heavy metal content from the two gulfs. The data used in this study is secondary data, which consists of data on heavy metals, current velocity, pH and water temperature. The period of data used in this research are from 2016 to 2019, The method used in this study is the GIS method with descriptive analysis. The comparison of concentrations from two bays shows a higher mean of concentration value of heavy metals cadmium (Cd) in Semarang Bay (2016, 2017, 2019) and heavy metals of copper (Cu) in Jakarta Bay (2016 and 2018). Meanwhile, the concentration value of heavy metal lead (Pb) was higher in Jakarta Bay (2016, 2017, 2018), yet in 2019, the two locations have the same concentration value of heavy metal lead (Pb).Keywords:Coastal areaDistributionHeavy metalsJakarta BaySemarang Bay